Hepatitis C Treatment Among Primary Care and Specialty Providers: A Single Center Study, 2015 to 2022 - Anna Scialli; Sammy Saab; Anabel Salimian; Debika Bhattacharya; David Goodman-Meza (SAGE Publishing, 2024)
Introduction: Despite national goals to eliminate Hepatitis C (HCV) and the advancement of curative, well-tolerated direct-acting antiviral (DAAs) regimens, rates of HCV treatment have declined nationally since 2015. Current HCV guidelines encourage treatment of HCV by primary care providers (PCPs). Payors have reduced restrictions to access DAAs nationally and in California however it remains unclear if the removal of these restrictions has impacted the proportion of PCPs prescribing DAAs at a health system level. Our objective was to examine the proportion of DAAs prescribed by PCPs and specialists and to describe the population receiving treatment in a single health system from 2015 to 2022. Methods: We examined the proportion of DAAs prescribed by PCPs and specialists and the population receiving treatment through a retrospective analysis of claims data in the University of California, Los Angeles (UCLA) Health System from 2015 to 2022. We described number of prescriptions for HCV medication prescribed by PCPs and specialists by year, medication type, and physician specialty. We also described numbers of prescriptions by patient demographics and comorbidities. Results: A total of 1515 adult patients received a prescription for HCV medication through the UCLA Health System between 2015 and 2022. The proportion of patients receiving prescriptions for PCPs peaked at 19% in 2016, yet decreased to 5.7% in 2022, an average of 13% across all years. Median age of patients receiving treatment was 60 years old, and 56% of patients receiving HCV treatment had commercial insurance as their primary payer. Conclusions: HCV treatment declined from 2015 to 2022 among specialists and PCPs in our health system. Older patients comprised the majority of patients receiving treatment, suggesting a need for novel approaches to reach patients under 40, an age group with significant increases in HCV transmission.